Infrared drying kinetics of goldenberry (Physalis peruviana L.): effects of ultrasound, citric acid, microwave pretreatments on drying behaviour and quality attributes - Borucu, Elena; Doymaz, Ibrahim; Borucu, Mustafa (TAYLOR & FRANCIS INC, 2026)
This study examined the infrared drying behavior of goldenberry (Physalis peruviana L.) at four different power levels (50, 62, 74, and 88 W), with particular emphasis on the effects of pretreatment and sample thickness on drying kinetics and product quality. Ultrasound, citric acid immersion, and microwave pretreatments were applied prior to drying at 50 W in order to enhance mass transfer and improve color retention. The influence of sample thickness was further assessed by comparing the drying characteristics of whole and halved fruits. The results showed that halved samples required 33.3% less drying time than whole fruits, confirming the marked effect of thickness on drying behavior. The effective moisture diffusivity of untreated samples varied between 7.18 & times; 10-9 and 1.48 & times; 10-8 m2/s, whereas all pretreatments increased diffusivity and thereby promoted faster moisture removal. Among the pretreatment methods, ultrasound proved to be the most effective, yielding the shortest drying time, superior color preservation, and the highest rehydration ratio. An increase in infrared power led to a decrease in total color difference, indicating that shorter drying periods contributed to improved color retention. In general, all pretreatments enhanced the visual quality of dried goldenberries, while citric acid treatment produced a color most similar to that of the fresh fruit. Overall, the findings demonstrate that infrared power, pretreatment strategy, and sample thickness are critical factors in improving both drying efficiency and the quality attributes of dried goldenberry.
Keywords: Activation energy; color; goldenberry; infrared drying; rehydration ratio; Engineering